Social Cognition Capacities as Predictors of Outcome in Mentalization-Based Treatment (MBT) - Kvarstein, Elfrida H.; Folmo, Espen; Antonsen, Bjørnar T.; Normann-Eide, Eivind; Pedersen, Geir; Wilberg, Theresa (Frontiers in Psychiatry, 2020)
Background: Mentalization-based treatment (MBT) is an evidence-based treatment for borderline personality disorder (BPD). Differences in treatment outcomes related to specific capacity of social cognition need further attention. This study aimed to investigate social cognition as a predictor of outcome. Method: The study included 31 BPD patients who completed a test of social cognition (Movie for the Assessment of Social Cognition, MASC) before outpatient MBT. The MASC-scores indicated a person’s theory of mind (ToM) and different error-types. During treatment repeated self-reports of alliance and clinical outcomes (symptoms, interpersonal problems, social functioning) were applied. Longitudinal analyses were based on Linear Mixed Models (n=24). Results: The most frequent error-type was excessive ToM (hypermentalizing). Higher levels of excessive ToM were associated with greater improvement of alliance over time and good clinical outcomes. Insufficient ToM errors and low levels of accurate cognitive ToM responses were both associated with poorer improvement over time. The subgroup with frequent insufficient ToM errors had a larger total number of ToM errors. Insufficient ToM errors were associated with more childhood trauma, comorbid avoidant PD traits and/or PTSD, extensive prior treatment and/or treatment irregularity. Conclusion: This study demonstrates considerable variation of social cognitive capacity among BPD patients and good outcomes for patients with mainly ToM errors of hypermentalizing. It also indicates that poorly responding patients may represent a cohort with more severe problems of social cognition.